KEPERCAYAAN DIRI DAN PERILAKU DIET TERHADAP BODY DISSATISFACTION PADA ANGGOTA AEROBIK - Azzahra, Virginian Fatima; Muslimah, Alfiana Indah; Ekasari, Agustina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2024)
This research aims to determine body dissatisfaction which is influenced by self confidence and diet behavior. This research is quantitative research with a research design using correlation research and multiple linear regression. The research subjects were 86 respondents who were members of aerobics at Aeromix Studio Ayu Bekasi using a simple random sampling technique. Data collection in this research used psychological scales and interviews. The instruments used were psychological scales consisting of the Body Shape Questionnaire (BSQ-34) scale from Cooper, Taylor, Cooper and Fairbum (1987), a self-confidence scale and a diet behavior scale. The instrument reliability test using the Cronbach's Alpha formula produced a ralpha value = 0.969 for the body dissatisfaction scale, a ralpha value = 0.888 for the self confidence scale and a ralpha value = 0.783 for the diet behavior scale. Data analysis in this study used the Spearman rank correlation technique and multiple linear regression tests to test the hypothesis. The results of research between the variables of self-confidence and dietary behavior on body dissatisfaction show an F value of 17.155 with the results of the significance test showing a value of 0.000 (Sig, ≤ 0.05). Self confidence and diet behavior simultaneously influence body dissatisfaction by 29.2%, while 70.8% is influenced by other variables not examined in this study.